Perception of the Mathematics of Investment Curriculum and Cash Management Practices Among BSED-Mathematics Students: Basis for a Curriculum Action Plan - Marasigan, Mary Joy; Chavez, Qiarrah Syrah (JPAIR Multidisciplinary Research, 2026)
This study examined the relationship between BSED–Mathematics students’ perceptions of the Mathematics of Investment curriculum and their level of cash management at City College of Calapan. Grounded in Self-Perception Theory, the Theory of Planned Behavior, and the Theory of Reasoned Action, the research aimed to determine how students’ understanding of the course objectives, content, and required competencies relates to their cash management practices. Employing a quantitative descriptive-correlational research design, the study involved 121 purposively selected BSED–Mathematics students who had completed the Mathematics of Investment course. Data were gathered using a validated researcher-made questionnaire and analyzed through the mean and Pearson’s Product-Moment Correlation Coefficient. The findings revealed that students generally perceived the Mathematics of Investment curriculum positively in terms of its objectives, content, and required competencies, while their cash management skills were rated high across school-related, lifestyle-related, and personal financial aspects. Correlational analysis revealed a mixed pattern: specific curriculum dimensions were significantly related to specific cash management dimensions—most notably objectives with lifestyle-related finances, content with personal-related finances, and required competencies with school-related finances—yet the overall relationship between students’ perception of the curriculum and their level of cash management was very low and not statistically significant (r = .08, p = .119). This suggests that while certain aspects of the curriculum are meaningfully associated with specific financial behaviors, students’ cash management is largely shaped by factors beyond curriculum perception alone. Based on these findings, a curriculum action plan was developed to strengthen the weaker areas of curriculum delivery—particularly compound interest computation and financial terminology—and to promote outcomes-based teaching and learning that supports financial literacy and long-term financial well-being among future educators.
Keywords: Mathematics of Investment; financial literacy; curriculum perception; cash management; lifestyle